Portuguese tourism demand - Leitão, Nuno Carlos (2020)
This study measures the impact of economic determinants on the international demand for tourist services in Portugal. A panel data set of 15 European countries over the period 1995-2003 is used. This article used appropriate panel data techniques of real per capita income, the price index of tourism service, geographical distance on demand for Portugal tourism services. In contrast to previous studies, this manuscript used a dynamic panel data to solve the problems of serial correlation and endogeneity. The estimate of the relative price elasticity of demand for Portugal's is 0.35 in the short run and 0.37 in the long run. The corresponding estimates for income elasticity on demand are 0.402 and 0.391 respectively.